2020
DOI: 10.1093/molehr/gaaa068
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles miRNA-21: a potential therapeutic tool in premature ovarian dysfunction

Abstract: Chemotherapy induces an irreversible premature ovarian dysfunction (POD). Amniotic fluid mesenchymal stem cells (AFMSCs) can rescue fertility; however, the notion that stem cells can rejuvenate follicles is highly controversial due tthe predetermined ovarian reserve. This study aims to isolate AFMSC-derived extracellular vesicles (EVs) and investigate their abundancy for the anti-apoptotic miRNA-21 as a means of ovarian restoration. Female rats were divided into healthy controls and POD-induced groups. The POD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…In 2012, Liu et al [119] proved that CD44 + / CD105 + hAFMSCs transplanted into the ovaries of mice with POF survived for at least 3 weeks, and CD44 + / CD105 + hAFMSCs underwent normal cycles of cell proliferation and self-renewal in ovarian tissues of mice with POF. HAFMSC-derived exosomes (hAFMSCs-EXOs) enhanced follicular regeneration, regular estrous cycles, and AMH level through the miRNA 21/PTEN/caspase 3 signaling pathway [120]. Compared with hBMMSCs, hAFMSCs secreted higher levels of exosomes.…”
Section: Human Amniotic Fluid Mscs (Hafmscs) Characteristics Of Hafmscsmentioning
confidence: 99%
“…In 2012, Liu et al [119] proved that CD44 + / CD105 + hAFMSCs transplanted into the ovaries of mice with POF survived for at least 3 weeks, and CD44 + / CD105 + hAFMSCs underwent normal cycles of cell proliferation and self-renewal in ovarian tissues of mice with POF. HAFMSC-derived exosomes (hAFMSCs-EXOs) enhanced follicular regeneration, regular estrous cycles, and AMH level through the miRNA 21/PTEN/caspase 3 signaling pathway [120]. Compared with hBMMSCs, hAFMSCs secreted higher levels of exosomes.…”
Section: Human Amniotic Fluid Mscs (Hafmscs) Characteristics Of Hafmscsmentioning
confidence: 99%
“…And then a study in mice revealed higher level of AKT, P-AKT, VEGF, and IGF in UCMSC-MVs-treated groups compared to non-treated POI group, implying that UCMSC-MVs might induce angiogenesis and activate the PI3K/AKT signaling pathway in ovaries ( 38 ). Notably, PTEN, which regulated PI3K/AKT pathway negatively, was downregulated after injected BMSC-EVs or AFMSC-EVs in POI rat models ( 40 , 46 ), suggesting that MSC-EVs might ameliorate GCs apoptosis in POI via PTEN-PI3K pathway. Moreover, MSC-EVs could suppress SIRT families (including SIRT4 or SIRT7) and P53 to reduce cisplatin or cyclophosphamide (CTX)-induced GCs apoptosis ( 36 , 41 , 44 ).…”
Section: Methodsmentioning
confidence: 99%
“…Functionality of the ovaries through the production of hormones and gametes guarantees the health of the female reproductive system ( Kim et al, 2018 ). In the ovarian follicle, the oocyte is surrounded by granulosa cells and cumulus cells that allow oocytes to survive, grow and mature through molecular and intercellular communications ( Thabet et al, 2020 ). Proliferation and differentiation of granulosa cells is essential for the continuous development of follicles from primary, secondary, tertiary antral follicles up to ovulation ( Li et al, 2019 ).…”
Section: Ovarian Diseasesmentioning
confidence: 99%